Production of a recombinant membrane protein in an Escherichia coli strain for the whole cell biosynthesis of phenylacetic acids - Oelschlägel, Michel; Heiland, Claudia; Schlömann, Michael; Tischler, Dirk (Biotechnology reports (Amsterdam, Netherlands), 2015)
[Display omitted] The styrene oxide isomerase (SOI) represents a membrane-bound enzyme of the microbial styrene degradation pathway and has been discussed as promising biocatalyst. It catalyzes the isomerization of styrene oxide to phenylacetaldehyde. In this study a styC gene, which encodes the SOI of Rhodococcus opacus 1CP, was optimized for optimal expression in Escherichia coli BL21(DE3) pLysS. The expression of this synthetic styC was investigated and subsequently optimized. Highly active biomass was obtained yielding an SOI activity of 44.5±8.7Umg−1 after 10h. This represents the highest SOI activity reported for crude cell extracts of SOI-containing bacterial strains. Remarkably, this biomass can be applied as whole cell biocatalyst for the production of phenylacetic acids from styrene oxides. In the case of non-substituted styrene oxide, nearly 730mgl−1 phenylacetic acid (∼85% yield) was formed over a period of 20 days.